If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(t + -3) + 8t = 7(3t + 2) + -12 Reorder the terms: 13(-3 + t) + 8t = 7(3t + 2) + -12 (-3 * 13 + t * 13) + 8t = 7(3t + 2) + -12 (-39 + 13t) + 8t = 7(3t + 2) + -12 Combine like terms: 13t + 8t = 21t -39 + 21t = 7(3t + 2) + -12 Reorder the terms: -39 + 21t = 7(2 + 3t) + -12 -39 + 21t = (2 * 7 + 3t * 7) + -12 -39 + 21t = (14 + 21t) + -12 Reorder the terms: -39 + 21t = 14 + -12 + 21t Combine like terms: 14 + -12 = 2 -39 + 21t = 2 + 21t Add '-21t' to each side of the equation. -39 + 21t + -21t = 2 + 21t + -21t Combine like terms: 21t + -21t = 0 -39 + 0 = 2 + 21t + -21t -39 = 2 + 21t + -21t Combine like terms: 21t + -21t = 0 -39 = 2 + 0 -39 = 2 Solving -39 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7(x-2)-5(x-2)=-2(x-4) | | 3=6x-2x+3 | | 2.50x=1342.5. | | 18a+3=(0+0) | | 5y-18=-25 | | -4(x-7)=52 | | 7-(5-8x)=26 | | lny=1.2+0.8lnx | | 5*-0.6-3= | | 0.75x+0.05(20-x)=0.10(122) | | y-(-7)=-4x-0 | | 5x-35=12x+30 | | 7-5(5-8x)=26 | | 3(x+4)=3x+7 | | 8x-131=94-x | | 7(m+5)=14 | | 4--z=6 | | 15-5x=2x-8+15 | | 2*-.6+3= | | 18X+13-5X= | | 10x-1=2x+35 | | 3(-2m-3)=-6(5+m)+7m | | y-16=3x-15 | | 4-3y=2(2y+5)+6 | | 18and+13-5n= | | 0.12(24)+0.02x=0.06(24+x) | | 2.25t+5+13.5t=14 | | 20-2a=2(4+5a) | | 3*-.6= | | 5.4q-4.3-7.2q=-2.7-1.8q-1.6 | | 2(m-6)=4+3(3m-7) | | -4.52=3.2+1.48 |